PENGARUH MODEL PEMBELAJARAN COURSE REVIEW HORAY (CRH) TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS V SD INPRES 12/79 PATTIRO SOMPE KABUPATEN BONE - Liana, Herliana (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
This research is a quantitative research with a pre-experimental type of research using a one group pretest-posttest research design which aims to determine whether there is a significant effect of using the Course Review Horay (CRH) learning model on the Indonesian language learning outcome of class V students at SD Inpres 12/79 Pattiro Sompe Bone Regency. The variables in this research are the course review horay (CRH) learning model (Independent variable) and Indonesian language learning outcomes (dependent variable). The research population was all fifth grade students at SD Inpres 12/79 Pattiro Sompe with a sample of 32 sstudents selected based on the saturated sampling technique. Data collection techniques use tests using descriptive statistical analysis techniques and inferential statistics. Based on the results of descriptive statistical analysis, the pretest average was 39,84, while he posttest average was 76,56. The data obtained was then analyzed using the Paired Sample t-Test with a significance level of 5%. From the results of data analysis, tcount was 21.932 > ttable 2.039. so tcount > ttable then H0 is rejected and H1 is accepted, so it can be concluded that there is a significant influence of using the Course Review Horay (CRH) learning model on the Indonesian language learning outcomes of class V students at SD Inpres 12/79 Pattiro Sompe, Bone Regency.